Pengaruh Earning Per Share (EPS), Price Earning Ratio (PER), Price To Book Value (PBV), dan Debt To Equity Ratio (DER) Terhadap Harga Saham Pada Perusahaan Indeks Saham Syariah Indonesia (ISSI) - Nuri Firdaus Amaliyah; Seger Priantono; Dyah Perwitasari (Ecobuss, 2017)
This research aims to know the influence of Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER) on a stock price of Indonesian Sharia Stock Index (ISSI) company registered at IDX. The type of research used is associative and quantitative. The sample of this research is using 30 companies selected based on purposive sampling method with observation period 2012-2016. The data used are secondary data sourced from financial statement data in IDX, with data collection method in the form of documentation and literature study. The data analysis used is multiple regression analysis. The result shows that Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER) simultaneously affect stock price with coefficient value of Earning Per Share (EPS) is 0,002, Price Earning Ratio (PER) is 0,0001, Price to Book Value (PBV) is 0.004, and Debt to Equity Ratio (DER) is -0,025. Partially Earning Per Share (EPS) have an effect on stock price, while Price Earning Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER) partially have no effect to a stock price. And Earning Per Share (EPS) is the dominant variable to the stock price with t value is 14.724. Keywords: Debt to Equity Ratio (DER), Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), Stock Price